Pandangan dunia dalam webtoon sekotengs: kajian strukturalisme genetik lucien goldmann - Fitri Merawati; Muhammad Yusa Dwi Putranto (BAHASTRA, 2020)
This study aims to describe the human fact, collective subject, and world view contained in the Sekotengs webtoon. This webtoon is popular with 4.6 million readers. This type of research is qualitative, centered on description. The subject of this research is Lifina's  Sekotengs webtoon, while the object of this research is the author's humanity fact and worldview. The theory used is Lucien Goldmann's genetic structuralism. The results of this study indicate that in the Sekotengs Webtoon there are two types of humanity facts, namely the fact of humanity, cultural creations and the fact of humanity social activities. There are 36 data on humanity in terms of cultural creation, while 27 in humanity data on social activities. Collective subjects in the Webtoon Sekotengs are dominated by high social class, which is as much as 10 data. The main character and the side character are described as rich people. The depiction of the poor can be found through only a few patient figures. Besides this webtoon has a worldview of materialism. Lifina through Webtoon Sekotengs considers that someone who is considered handsome or beautiful and has a high social class will be more admired by others and become an idol.